"Les lieux de mémoire" and Pierre Nora's writing of French national history. Issue 2 (2nd April 2020) - Yanhong, Huang
Abstract: After World War II, the orientation toward economic and social history of France's new history weakened the traditional national history narrative. A series of major social and political changes in French society of the 1970s reduced consciousness of the nation-state, and individualized historical memory and counter-memories and identities became increasingly prominent as the historical memory of the Lavissian nation-state fragmented. It was in this context that les lieux de mémoire emerged; Pierre Nora seeks to pursue a national consciousness without nationalism by recalling the realms of memory. Although inspired by Ernest Lavisse's L'histoire de France, this study, more inclusive than Lavisse's, is a reflective "second-degree history" that attempts to seek identity in the "inheritance" of national memory following the decay of nationalist ideology. The proposed lieux de mémoire implies a profound change in the past, present and future relationships of French national history, a change that undermines historical continuity. This can be regarded as a new marker for a historical system: "presentism."